Tutkimus- ja tuotekehitysinvestointien verotuki - Tarmo Valkonen (The Research Institute of the Finnish Economy (ETLA), 2007)
The data were collected via a web-based survey tool in the autumn of 2006. The study takes into consideration the viewpoint of VC investors as it focuses on Finnish VC companies (private sector VCs), public sector VC organisations and informal investors (business angels). An effort was made to collect data from foreign investors active in Finland though they did not respond actively. Major findings of the study included the observation that private sector VCs were the most and public sector VCs the least active in monitoring their portfolio companies. Informal VCs were less active than expected. The different investor types had distinct profiles in providing management support and advice. Overall, private sector VCs evaluated the nonfinancial support they provided as the most and public sector VCs the least important for the success of their portfolio companies while informal VCs were between these extremes. These findings differed from those obtained in our study on the value-adding function of VCs in biotechnology, according to which informal VCs were found to have the highest overall value-added and kept closest contacts with their investee firms.
Keywords: H25; O1; O4; 330; Venture Capital; Forschungs- und Technologiepolitik; Forschungsfinanzierung; Steuerbegünstigung; OECD-Staaten